Multiparty Computations in Non-private Environments - Liśkiewicz, M. (General Theory of Information Transfer and Combinatorics, 2006)
Private multi-party computations is an intensively studied subject of modern cryptography. In general, private computation can be defined as follows: Consider a set of players, where each player knows an individual secret. The goal is to compute a function depending on these secrets such that after the computation none of the players knows anything about the secrets of others that cannot be derived from his own input and the result of the function. To compute the function, the players exchange messages with each other using secure links. For a formal definition of cryptographically secure privacy see [8] and for privacy in information theoretic sense see [5,2].